Differential immune responses in new and old fruit fly-parasitoid associations: Implications for their management - Gwokyalya, Rehemah; Herren, Jeremy K.; Weldon, Christopher W.; Khamis, Fathiya M.; Ndlela, Shepard; Mohamed, Samira Abuelgasim (Frontiers in Physiology, 2022)
The oriental fruit fly, Bactrocera dorsalis (Hendel), and marula fruit fly, Ceratitis cosyra (Walker), are major fruit-infesting tephritids across sub-Saharan Africa. Biological control of these pests using parasitic wasps has been widely adopted but with varying levels of success. Most studies investigating host-parasitoid models have focused on functional and evolutionary aspects leaving a knowledge gap about the physiological mechanisms underpinning the efficacy of parasitoids as biocontrol agents of tephritids. To better understand these physiological mechanisms, we investigated changes in the cellular immune responses of C. cosyra and B. dorsalis when exposed to the parasitic wasps, Diachasmimorpha longicaudata (Ashmaed) and Psyttalia cosyrae (Wilkinson). We found that B. dorsalis was more resistant to parasitisation, had a higher hemocyte count, and encapsulated more parasitoid eggs compared to C. cosyra, achieving up to 100% encapsulation when exposed to P. cosyrae. Exposing B. dorsalis to either parasitoid species induced the formation of a rare cell type, the giant multinucleated hemocyte, which was not observed in C. cosyra. Furthermore, compared to P. cosyrae-parasitized larvae, those of both host species parasitized by D. longicaudata had lower encapsulation rates, hemocyte counts and spreading abilities and yielded a higher number of parasitoid progeny with the highest parasitoid emergence (72.13%) recorded in C. cosyra. These results demonstrate that cellular immune responses are central to host-parasitoid interaction in tephritid fruit flies and further suggest that D. longicaudata presents greater potential as a biocontrol agent of B. dorsalis and C. cosyra in horticultural cropping systems.